PENGARUH DAYA TARIK BRAND AMBASSADOR DAN INTENSITAS KOMUNIKASI ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP MINAT BELI PRODUK CLEO - Ainun Faizah Ainun Faizah; Djoko Setyabudi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
The increasing trend of healthy lifestyles in Indonesia has driven the consumption of bottled drinking water and intensified industry competition. Cleo utilizes celebrity family brand ambassadors and electronic word of mouth (e-WOM) communication to strengthen its position as a healthy drinking water choice for families. However, a gap remains, as indicated by consumer skepticism toward product claims. This study aims to analyze the influence of brand ambassador attractiveness and e-WOM intensity on purchase intention toward Cleo products using the source attractiveness model and integration information theory. The research employs a quantitative explanatory approach with purposive sampling of 100 respondents aged 18–35, and data are analyzed using simple linear regression. The results show that both variables have a positive effect on purchase intention, with brand ambassador attractiveness having a more dominant influence than e-WOM intensity.